Tendencies in the Historiography of Latvian Philosophy. - Hiršs, Andris (Problems / Problemos, 2023)
This article aims to investigate tendencies in the historiography of Latvian philosophy in the past three decades. This article focuses on the history of ideas and intellectual history as two different approaches in the field of the history of philosophy. After the dissolution of the Soviet Union, the term "history of ideas" gained popularity in the Latvian cultural discourse. Historians of philosophy were highlighting the close ties between Western and Latvian cultures. However, during the last decade, the approach of intellectual history has been gaining popularity among the Latvian historians of philosophy.